How to make z the subject of the formula?

z=y(zy)x

2 Answers
Feb 17, 2018

z=y2xy

Explanation:

Expand the expressions and then factor out z:

z=y(zy)x

z=yzy2x

zx=yzy2

zxyz=y2

z(xy)=y2

z=y2xy

Or, if you would like to rearrange the terms:

z=1y2xy

z=1y2xy

z=y21(xy)

z=y2x+y

z=y2yx

Feb 17, 2018

z=(y2xy)

Explanation:

Firstly, multiply xandz =xz
Then multiply y(zy) which equals to yzy2
Shift yz to the left, zxzy=y2
Then take out z, z(xy)=y2\
Then divide y2 by xy, z=(y2xy)
So, z=(y2xy)